2013
DOI: 10.1155/2013/938081
|View full text |Cite|
|
Sign up to set email alerts
|

Stevioside fromStevia rebaudianaBertoni Increases Insulin Sensitivity in 3T3-L1 Adipocytes

Abstract: Stevioside from Stevia rebaudiana has been reported to exert antihyperglycemic effects in both rat and human subjects. There have been few studies on these effects in vitro. In this paper, radioactive glucose uptake assay was implemented in order to assess improvements in insulin sensitivity in 3T3-L1 cells by elevation of glucose uptake following treatment with stevioside. Oil Red-O staining and MTT assay were utilized to confirm adipocyte differentiation and cell viability, respectively. Findings from this r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 20 publications
0
14
0
1
Order By: Relevance
“…Stevia rebaudiana Bertoni and its glycosides are known not only as natural, noncaloric sweeteners but also for their antihypertensive, anti-inflammatory, immune-modulatory, and antihyperglycaemic effects [ 9 ]. In particular, the hypoglycaemic, antidiabetic, and insulin-like properties of steviol glycosides have been investigated in 3T3-L1 adipocytes [ 40 ], in L6 myoblasts [ 21 ], and in cancer-derived cell lines [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Stevia rebaudiana Bertoni and its glycosides are known not only as natural, noncaloric sweeteners but also for their antihypertensive, anti-inflammatory, immune-modulatory, and antihyperglycaemic effects [ 9 ]. In particular, the hypoglycaemic, antidiabetic, and insulin-like properties of steviol glycosides have been investigated in 3T3-L1 adipocytes [ 40 ], in L6 myoblasts [ 21 ], and in cancer-derived cell lines [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…ions. Mohd-Radzman et al (2013) observed that stevioside has direct effects on 3T3-L1 insulin sensitivity via increase glucose uptake and enhanced expression of proteins involved in insulin-signaling pathway. Increased insulin secretion is connected with the closure of ATP-dependent potassium channels, which results in the depolarisation of pancreatic beta cells and activation of Ca 2?…”
Section: Hypoglycemic Effectmentioning
confidence: 98%
“…The report confirmed the stevioside noncytotoxicity and increased glucose uptake activity in insulin resistant states, sometimes greater than that observed in the treated group with antidiabetic agent. This S. rebaudiana extract was found to have direct effects on insulin sensitivity through an increase in glucose uptake and increased expression of proteins linked to the insulin signaling pathway (Mohd‐Radzman et al, ). Other authors have demonstrated a direct insulinotropic effect of glycoside stevioside (Jeppesen, Gregersen, Alstrup, & Hermansen, ).…”
Section: Pharmacokinetics Pharmacodynamics and Toxicologymentioning
confidence: 99%
“…Thus, it was concluded that S. rebaudiana extracts could mimic insulin effects by modulating PI3K/Akt pathway (Rizzo et al, ). Similarly, in another study, the radioactive glucose uptake assay was used to assess the progress of insulin sensitivity in 3T3‐L1 cells by elevation of glucose uptake, following treatment with stevioside (Mohd‐Radzman, Ismail, Jaapar, Adam, & Adam, ). The report confirmed the stevioside noncytotoxicity and increased glucose uptake activity in insulin resistant states, sometimes greater than that observed in the treated group with antidiabetic agent.…”
Section: Pharmacokinetics Pharmacodynamics and Toxicologymentioning
confidence: 99%